Copywriting Membuat Landing Page Sebagai Advertising Essentials di DSAA Group, Surabaya (Current Research in Education: Conference Series Journal, 2023)
The important role of copywriting in advertising agencies must be to be able to find advertising concepts. The suitability of the advertising concept with the product is also with the demands to always think creatively. Adjustment of advertisements with products issued by the company becomes the main point in copywriting. By using a profession that plays a role in mastering the art of the word, copywriting is in charge of creating and shaping advertisements. Also, copywriting skills in the realm of information technology in the field of internet programming are very much-needed. Writing ad copy created to promote products from DSAA group companies as a form of trademark content marketing. The landing page was chosen as a promotional medium to attract readers. Research purposes undertaking direct activities in field practice to understand directly the needs of the industry by working on creating landing pages that must be able to create advertising essentials in the DSAA group company. Using quantitative description research methods describe the reality that is happening without explaining the relationship between variables. With the understanding that is owned and learned from the DSAA group's products, making a landing page is very appropriate for marketing with information recording techniques that can be used to find potential customers again with other products. The conclusion is that a copywriter must have innovative and creative ideas and ideas in making landing pages to persuade potential buyers to buy products from the DSAA group.